Efektivitas Penerapan Teknik Umpan Balik Dalam Meningkatkan Motivasi Belajar Peserta Didik - Witta Perdana Putri; Salma Fauziyah; Muhammad Usamah Ibnu Khair; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
the article aims to describe (tell) the effectifenes of implementing feedback techniques in increasing student learning motivation. This research uses a library method ( library research ), and is qualitative in nature because the data collected uses textual analisis contained in educational books and journals which relate to feedback techniques in student learning motivation. The results of this research are:firstly in this study we obtained secondly the purpose and function of feedback, and thirdly, feedback techniques in increasing student’s learning motivation.